2021
DOI: 10.1155/2021/8996673
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Optimization of Tumor Disease Monitoring in Medical Big Data Environment Based on High‐Order Simulated Annealing Neural Network Algorithm

Abstract: With the development of medical informatization, the data related to medical field are growing at an amazing speed, and medical big data appears. The mining and analysis of these data plays an important role in the prediction, monitoring, diagnosis, and treatment of tumor diseases. Therefore, this paper proposes a clustering algorithm of the high-order simulated annealing neural network algorithm and uses this algorithm to extract tumor disease-related big data, constructs training set according to the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As medical technology advances, the usage of crucial medical data for monitoring, prevention, and diagnosis of infectious tumors upsurges. This process usually depends upon managing, collecting, and analyzing the data set for infectious tumor diagnosis and treatment [2,3,4]. The timely detection of a brain tumor can have a positive impact on the patient's chances of survival and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…As medical technology advances, the usage of crucial medical data for monitoring, prevention, and diagnosis of infectious tumors upsurges. This process usually depends upon managing, collecting, and analyzing the data set for infectious tumor diagnosis and treatment [2,3,4]. The timely detection of a brain tumor can have a positive impact on the patient's chances of survival and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…treatment (Akram et al, 2021;Houssein et al, 2021a;Zhang et al, 2021;Javed et al, 2022;Rizwan et al, 2022b). Cancer is one of the most significant health issues and challenges currently threatening people's lives.…”
mentioning
confidence: 99%